Exploratory Study on the Motivational Factors of Contract FarmingS. - Kumar, Arun; Singh, Premlata (Indian Journal of Extension Education, 2010)
Contract farming is practised in many crops like cotton and coleus in Tamil Nadu. The objective of the study was to identify the motives of the farmers and the contracting firms for entering into contract farming. The study was conducted in Salem and Viluppuram with 80 contract farmers. Assured price, immediate payment, reduce the credit burden, input assistance are the four important motives of the contract farmers to enter contract farming. Input assistance, increased income, assured market, financial assistance, recognition among friends and relatives, success, knowledge on new technologies, security are the other motives reported by the farmers. In the case of the contracting firm, suitability of crop, interest in particular crop, good remuneration, motivation to do something good for the farmers community, assured and timely supply of raw materials, demand for the fine and super fine varieties and the quality produces are the found motives for entering into the contracting agreement with the farmers.